CORRELATION AND REGRESSION OF METROLOGICAL FACTORS WITH SUGARCANE SMUT DISEASE CAUSED BY SPORISORIUM SCITAMINEA (SYN. USTILAGO SCITAMINEA) - PRATEEKSHA MEHRA; R. K. SAHU (The Bioscan, 2015)
Smut caused by Sporisorium scitamineum (Syn: Ustilago scitaminea) is an important fungal disease widely prevalent in tropical India causing huge monetory losses. Sugarcane crop requires a hot and humid climate for its development which is also conducive for the development of various diseases. The disease incidence was studied for both the infection cycles for primary infection cycle the maximum temperature showed positive significant correlation (0.074) while, in case of secondary infection cycle average relative humidity showed negatively significant correlation (-0.683) and there was non significant correlation obtained in case of rainfall, wind velocity and sunshine. Though disease development was observed at 22.3°C maximum temperature, it was rapid at above 34.8ºC and slow between 11.5ºC - 22.2ºC which was favoured by average relative humidity 65% - 76.5%.